Strategi Manajemen Komunikasi Dalam Menghadapi Krisis Kepercayaan Masyarakat Terhadap Rendahnya Kualitas Pelayanan Rumah Sakit Pemerintah Studi Kualitas Pelayanan Kesehatan Pada RSUD Abdul Manaf Kota Jambi - Dedek Kusnadi (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
Trust in the context of communication is a description of the hope that words, promises, verbal or written statements from other individuals or groups can be trusted. In an organization or institution, trust is the most important capital in its survival. Organizations or institutions will not be able to survive for long if they do not gain the trust of the community. This public trust will be one of the factors in the occurrence of a crisis. For this reason, it is considered very important for communication strategies in dealing with crises that occur in institutions and organizations. The crisis of confidence experienced by most government hospitals regarding the quality of health services has an impact on the existence and existence of Abdul Manaf Hospital, Jambi City, which incidentally is also the core of public health services in Jambi City. With the increasingly mushrooming growth of competitors such as private clinics and hospitals, this is used as a benchmark for continuous improvement in service quality. The tendency of people to prefer clinics, private hospitals or to seek treatment in extreme conditions abroad, this is evidence that government hospitals are starting to be abandoned by the public in entrusting their health. The communication strategy of government hospital public relations practitioners must be able to overcome this so that it does not have a broad impact on the continuity of health institutions in Indonesia.